Formulation and Evaluation of Sustained Release Microcapsule of Metronidazole - Leo, Natassya Manda; Bangun, Hakim; Harahap, Urip (International Journal of Science, Technology & Management, 2022)
The oral conventional metronidazole dosage forms have a short duration of action due to gastric emptying process, hence the treatment of ulcus pepticum using metronidazole become less effective. Due to retaining the dosage form in the stomach, a preparation form of sustained released drug delivery systems has been developed. The aim of this study was to developed a sustained released drug delivery systems of metronidazole using alginate and chitosan as polymers that could last longer in stomach. The formulation consisted of variatons in chitosan 0.5%, 0.75% and 1%. The drug released test was carried out using paddle method in simulated gastric medium pH 1.2 at 37°C. The dissolution test results showed that formula with 0.75% of chitosan giving the best sustained released effect and the kinetics drug realeased of microcapsule followed Higuchi order. Based on the results of the study, it can be concluded that microcapsules of metronidazole with a combination of alginate and chitosan can be prepared as sustained released formulation.